Functional porous carbons for zinc ion energy storage: Structure-Function relationship and future perspectives - Zhang, Hanfang; Zhang, Jiahe; Liu, Yanran; Feng, Feng; Zhang, Yingge; Sun, Li; Zhang, Yihe (Coordination chemistry reviews, 2023)
•Functional porous carbon materials with various dimensions for Zn2+ storage.•The effects of microscopic morphology, pore size distribution and surface functional groups on the electrochemical behavior of electrode materials.•The properties and functions of various carbon materials are compared and discussed from the perspective of the interaction between electrolyte ions and electrode materials.•This review provides ideas for the future design of functional porous carbons as electrode materials for zinc ion energy storage. Zinc ion energy storage (ZIES) has attracted lots of focus in the field of energy storage, which has the advantages of simple preparation process, low-risk, and high energy density. Carbon materials have been widely studied and applied in Zn2+ storage because of abundant raw material sources, low production cost, good electrical conductivity, high chemical stability as well as diverse and controllable microstructures. Here, various types of porous carbon materials used in Zn2+ storage are reviewed, including zero-dimensional (0D) carbon nanomaterials like nanospheres or hollow structure, one-dimensional (1D) carbon nanomaterials like carbon nanofibers and carbon nanotubes, two-dimensional (2D) carbon nanomaterials like graphene, graphdiyne and graphene-like carbon nanosheets, and three-dimensional (3D) carbon nanomaterials like porous carbon balls, activated carbon, cross-linked sheet-like porous carbon and porous carbon materials with irregular microstructures. The structure-effect relationship is summarized from the analysis of the effects of microstructure, pore size distribution and surface functional groups on the electrochemical behavior of electrode materials. Besides, from the microscopic point of view of electrolyte ions interaction with electrode materials, the characteristics and functions of various carbon materials are compared and discussed. Finally, the challenges and prospects of carbon materials in ZIESs are summarized.